1987
DOI: 10.1111/j.2042-3306.1987.tb01373.x
|View full text |Cite
|
Sign up to set email alerts
|

Early development of gait asymmetries in trotting Standardbred colts

Abstract: Summary Ten trotting Standardbred colts were recorded by high‐speed cinematography at the ages of eight, 12 and 18 months. The horses were trotting on a treadmill operating at 4.0 m/secs. Five horses were subjected to a programme of intensified training from eight months of age, whereas the others were not trained and acted as controls. The films were analysed on a semi‐automatic film‐reading equipment and a number of variables used to demonstrate the gait symmetry were calculated and scaled by computer. Certa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 8 publications
1
44
0
Order By: Relevance
“…Temporal stride variables, when considered on their own, are of questionable value in detecting lameness: first, mild lamenesses do not show significant temporal deviations from the sound stride pattern, and, second, key parameters, such as StD or the time of diagonal advanced placement maintain their left-to-right symmetry with increasing lameness [30,59,73,74,84]. Temporal asymmetry is more commonly attributed to an individual locomotor pattern, also known as sidedness, handedness, or laterality [85,86]. Temporal parameters characterizing the airborne phase of the trot, such as contralateral step duration and SpD, change asymmetrically with increasing lameness [30,59,73].…”
Section: Discussionmentioning
confidence: 99%
“…Temporal stride variables, when considered on their own, are of questionable value in detecting lameness: first, mild lamenesses do not show significant temporal deviations from the sound stride pattern, and, second, key parameters, such as StD or the time of diagonal advanced placement maintain their left-to-right symmetry with increasing lameness [30,59,73,74,84]. Temporal asymmetry is more commonly attributed to an individual locomotor pattern, also known as sidedness, handedness, or laterality [85,86]. Temporal parameters characterizing the airborne phase of the trot, such as contralateral step duration and SpD, change asymmetrically with increasing lameness [30,59,73].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of right-handedness in humans, described across many cultures for thousands of years, is suggested to be evidence of the inherent nature of motor bias (Wilson, 1885;Dennis, 1958;Uhrbrock, 1973). Also, a study into young horses found they did exhibit motor bias in stride characteristics (Drevemo et al, 1987), and minimally handled horses were found to exhibit bias in favoured foreleg to initiate movement, direction of obstacle avoidance and rolling (Murphy et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Even with the extensive research of motor bias in humans, there are no clearly defined conventions for defining, testing or measuring handedness (Elliot and Roy, 1996), and a similar situation exists in the far fewer motor bias studies of horses. Some examples of the tests of motor bias used in past studies of horses include the advanced forelimb during grazing (McGreevy and Rogers, 2005;McGreevy and Thomson, 2006), lead stride pattern preference (Deuel and Lawrence, 1987;Williams and Norris, 2007), trotting gait asymmetries (Drevemo et al, 1987), and preferred foreleg to initiate movement at walk and trot, obstacle avoidance and rolling (Murphy et al, 2005). It is likely that because these tests vary (some considerably) in ways of measuring bias, they measure different characteristics of motor bias and therefore will result in conflicting conclusions as to the existence, degree and/or direction of motor bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heavier foals had longer stride lengths, and foals with greater height and length measurements relied more on stride frequency to increase velocity. Drevcmo et al [8] found an asymme try in the locomotion of 10 Standardbrcd colts recorded at the age of 8. 12 and 18 months.…”
Section: Introductionmentioning
confidence: 99%